Identification of problems and post-war recovery of tourism in Ukraine - But, Tetiana (Management and Entrepreneurship: Trends of Development, 2024)
Tourism is one of the sectors of the global economy most affected by the pandemic. At the same time, in 2022, having not yet fully recovered from the effects of quarantine restrictions, it was forced to face a completely new challenge - large-scale military operations on the territory of Ukraine. The purpose of the study is to identify the problems of tourism in Ukraine during the hostilities and ways of its post-war recovery. The methodological basis of the study was formed by general scientific and special methods of economic theory, in particular, methods of theoretical generalization and comparative analysis and synthesis in order to study all processes and phenomena of tourism in Ukraine in interdependence and interconnection. In the course of the study, statistical materials from the European Union and Ukraine were used. The growth of domestic tourism during the hostilities in Western and Central Ukraine was determined. Among the main problems of tourism during the war are: a high level of danger to the country during the war; the number of contaminated territories of Ukraine; war crimes against the environment; complete reorientation of some tourist infrastructure facilities from tourism activities to another direction; complete cessation of operation of some tourist enterprises due to lack of economic profitability; partners in tourism activities have ceased to function or do not receive tourists; tourist facilities in the occupation zone; destruction and damage to facilities Among the ways of post-war recovery are: involvement of small and medium-sized businesses in recovery; development of memorial tourism; focus of the post-war economic recovery program on technological modernization of the tourism industry; involvement of innovations in the implementation of specific instruments of state aid; promotion of investment in tourism in Ukraine and promotion of partnership with international companies; effectiveness of state policy in the post-war period for the restoration of tourism infrastructure and its improvement. JEL Classification: F5, Q53, Z32